1994
DOI: 10.1002/mus.880171207
|View full text |Cite
|
Sign up to set email alerts
|

Serial neurophysiological studies of intramuscular botulinum‐A toxin in humans

Abstract: To characterize the time course of intramuscular botulinum toxin-induced paresis, we serially performed electrophysiological measurements and recorded the sonographic size of an extensor digitorum brevis (EDB) muscle in 10 human subjects before and after injecting the EDB with 10 units of botulinum-A toxin. All EDB CMAPs decreased within 48 h, with peak decline at day 21 (8.3 +/- 3.1 mV to 3.0 +/- 0.9 mV). Decline of mean rectified voltage during maximal voluntary contraction of the EDB paralleled the change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 36 publications
(4 reference statements)
5
63
3
Order By: Relevance
“…The amplitude of the compound muscle action potential (CMAP) from the injected extensor digitorum brevis (EDB) muscle starts to decline 48 hours after the injection and the decline peaks between days 7 and 21. This inhibitory effect is long lasting and the CMAP amplitude usually requires more than 90 days for full recovery (Hamjian and Walker, 1994;Eleopra et al, 1998). In patients with hemifacial spasm the CMAP amplitude decrease correlates with the clinical benefits reported by the patient (Geller et al, 1989).…”
Section: Effects Of Bont-a On Peripheral Mechanismsmentioning
confidence: 93%
“…The amplitude of the compound muscle action potential (CMAP) from the injected extensor digitorum brevis (EDB) muscle starts to decline 48 hours after the injection and the decline peaks between days 7 and 21. This inhibitory effect is long lasting and the CMAP amplitude usually requires more than 90 days for full recovery (Hamjian and Walker, 1994;Eleopra et al, 1998). In patients with hemifacial spasm the CMAP amplitude decrease correlates with the clinical benefits reported by the patient (Geller et al, 1989).…”
Section: Effects Of Bont-a On Peripheral Mechanismsmentioning
confidence: 93%
“…Despite of the presence of post-void residual volume in our PD patients, we did not observe a significant reduction in other parameters accounting for detrusor muscle strength (PdetQmax, Qmax). It is well known that BoNT/A induces striated muscle denervation and weakness lasting about 3-4 months (Hamjian et al, 1994;Schiavo et al, 1994). In striated muscle it has been observed that the neurotoxin not only modulates extra-fusal component but also influences the altered muscle spindle afferent input (Abbruzzese et al, 2006;Currà & Berardelli, 2009;Rosales & Dressler, 2010;Trompetto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of excellent journals in the areas of Physical Medicine and Rehabilitation and Neurology, which are all appropriate venues, but M&N [3][4][5][6][7][8]10,11,13,15,16,19,20 has established itself as the journal with the largest number of published studies relevant to this emerging field, and its scope aligns perfectly with this new technology. Furthermore, neurologists, physiatrists, and clinical neurophysiologists, individuals who make up the majority of subscribers to the journal, are those most able to critique manuscripts and develop the technology.…”
mentioning
confidence: 83%
“…Ultrasound is well suited for the measurement of muscle dimensions such as thickness, even in small muscles, 4 and pathologic changes such as atrophy and hypertrophy. Ultrasound also can also sensitively detect changes in the echogenicity of muscle once histopathologic changes occur.…”
mentioning
confidence: 99%